Don't Say Practical Criticism, Say Fuck the Police. Issue 1 (April 2021) - Rose, Marika
Abstract : This article responds to John Wilkinson's piece, 'Moreover: Reading Alfred Starr Hamilton'. Opening with a consideration of the connections between language, law, economy, and freedom, it draws attention to Wilkinson's discussion of letters Hamilton wrote to the Montclair Police Department in 2020. These letters suggest that Hamilton's work might be usefully read as emerging from the economy of racial capitalism, and indicate the limits of his poetic search for freedom.